2013
DOI: 10.1088/0964-1726/22/9/094028
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the energy harvesting control for dielectric elastomer generators

Abstract: Energy harvesting using dielectric elastomers is an upcoming possibility to convert ambient energy into electric energy. Published results for energy harvesting cycles deal with charging and discharging of the polymer during a constant stretch state. However, real applications feature a continuously changing stretch and thus the time frames of the charging- and discharging-intervals have a considerable influence on the amount of harvested energy. This paper presents the calculation of the optimal charging- and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…15 As argued in the earlier studies on DEGs, the performance of the DEGs is not only limited by various failure modes such as electrical breakdown (EB) and loss of tension, but is also strongly affected by the material properties and other mechanisms such as material extensibility, material viscoelasticity, current leakage and loading congurations. 12,[15][16][17] The energy harvesting mechanism of a DEG, in fact, lies in the cyclic change of the capacitance, which is realized by stretching the DE and allowing it to recover. The larger the deformation of the DE is, the more the capacitance changes and thus a higher energy density is achieved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 As argued in the earlier studies on DEGs, the performance of the DEGs is not only limited by various failure modes such as electrical breakdown (EB) and loss of tension, but is also strongly affected by the material properties and other mechanisms such as material extensibility, material viscoelasticity, current leakage and loading congurations. 12,[15][16][17] The energy harvesting mechanism of a DEG, in fact, lies in the cyclic change of the capacitance, which is realized by stretching the DE and allowing it to recover. The larger the deformation of the DE is, the more the capacitance changes and thus a higher energy density is achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the capacitance change could also be maximized by changing the loading congura-tions as demonstrated by Huang et al 12 Particularly, it was reported by Huang et al 12 that the efficiency of the DEG is mainly limited by the viscous loss if the DEG operates in the safe range where electrical breakdown does not occur. However, most existing modeling works on the DEGs ignore the intrinsic viscoelasticity of the elastomers and only consider their hyperelastic properties, [15][16][17] which leaves many issues unsettled and may need further investigation. During the energy harvesting cycles of the DEGs, it is expected that the material viscoelasticity results in the change of the performance with the stretching and shrinking rates of the elastomer, as well as the stretch ratios.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Hoffstadt et al [13] conducted an optimisation of the conventional EH cycles and determined the ideal charging and discharging times for maximal energy gain in the optimised scheme.…”
Section: Energy Harvesting 44mentioning
confidence: 99%
“…Both types of cycles are synthetic, since neither force nor position is constant during charging and discharging in a real energy harvesting application. In this case, the changing generator force is directly coupled with the motion of the application, which results in a true generator cycle, as, for example, depicted in Figure 8(c) obtained when operating the test bench in HIL simulation (Hoffstadt et al, 2013).…”
Section: Realization Of Generator Cyclesmentioning
confidence: 99%